Exploring The Impact of Work-Life Balance, Organizational Commitment, And Work Discipline on Employee Productivity: A Study at PT Aeronusa Inti Raya in Denpasar - Handayani, Putu Ayu Rizza Putri; Rihayana, I Gede; Permadi, I Komang Oka (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Employee productivity is a critical component in ensuring the success and competitiveness of a company, particularly within the domain of logistics services, where promptness and effective work execution are paramount. The present study focuses on analyzing the influence of work-life balance, organizational commitment, and work discipline on employee productivity at PT Aeronusa Inti Raya in Denpasar. The research employs a quantitative approach, utilizing a survey method. The population of this study consists of 52 employees of PT Aeronusa Inti Raya in Denpasar. The sampling method employed is saturated sampling, whereby the entire population is considered the respondents. The data is collected through the implementation of a Likert scale questionnaire, while the subsequent data analysis employs the technique of multiple linear regression. The findings of the study suggest that work-life balance exerts a beneficial influence on employee productivity. Organizational commitment has been demonstrated to exert a positive and significant influence on work productivity. This suggests that employee engagement and loyalty play a substantial role in enhancing work performance. Conversely, work discipline has been demonstrated to exert a positive and significant effect on employee productivity. This suggests that adherence to established rules and punctuality can enhance work effectiveness. Concurrently, all independent variables have a substantial impact on the productivity of PT Aeronusa Inti Raya employees in Denpasar